Introduction: law containing violence: critical ethnographies of occupation and resistance. Issue 3 (2nd September 2017) - Duschinski, Haley; Bhan, Mona
ABSTRACT: This special issue of The Journal of Legal Pluralism and Unofficial Law brings together legal anthropologists and legal scholars who share a common commitment to understanding law's formative and constitutive role in relation to the social, cultural, and political dynamics of occupation. The authors draw upon and extend recent work on the emergence of new forms of military, multilateral, and humanitarian occupations, and their roles in reinforcing institutionalized violence against occupied peoples. Contributions in this volume treat occupation as a distinct object of legal and cultural analysis, revealing its similarities as well as its departures from colonial and postcolonial modes of state and military sovereignty. The special issue seeks to move beyond the limitations of existing cultural and legal frameworks and towards a context-driven mode of understanding the varied and flexible state practices of occupants and the legal texts and juridical decisions that shape the nature of their authority. At the same time, ethnographic analyses shed light on the collective memories and lived experiences that shape people's everyday relationships to the state and its military power.